Gambaran Kejadian Shivering Intra Operasi di Instalasi Bedah Sentral RSUD Jombang - Galih Pria Pambayun; Afrian Yohadi; Nabhani Nabhani (Jurnal Ventilator, 2023)
Sub Arachnoid Block (SAB) regional anesthesia produces a sympathetic block of muscle relaxation, and a sensory block against peripheral temperature receptors thereby inhibiting the compensatory response to temperature. A factor that can cause a decrease in core temperature and disruption of the information pathways coming from the first receptor is a sympathetic blockage that causes peripheral vasodilation. This research is a non-experimental quantitative research with correlational analytical research methods and cross sectional research design. The study sample amounted to 72 respondents of spinal anesthesia patients. Sampling with consequential sampling techniques, the statistical test used is distribution frekuency. Of the 16 people who experienced high blocks, (75%) experienced shivering and (25%) did not experience shivering. Of the 36 respondents who experienced moderate blocking, (58.3%) experienced shivering and (41.7%) did not shivering. Of the 20 respondents who experienced low spinal block, (70%) did not experience shivering and (30%) experienced shivering.. In conclusion, there is the height of the anesthetic spinal block and the incidence of intraoperative shivering at the Central Surgical Installation of RSUD Jombang.